Analisis Status Badan Hukum Dana Pensiun - Muhhamad Habibi Miftakhul Marwa (Fakultas Hukum Universitas Surabaya, 2020)
Act No. 11 of 1992 about the Pension fund states retirement funds as legal entities that manage and run retirement programs that promise retirement benefits when retired or full duty to participants. As a legal entity of course the pension fund is based on the subject of the law as a human being, which has the right and obligation to do legal action to the other party. Pension funds have a legal entity status and may conduct activities from the date of ratification by the Financial Services Authority. Reviewed from the theory or the terms of the legal entity, the status of the legal entity of the Pension Fund has fulfilled the requirements of the material or formyl in the establishment of pension funds, such as having a separate property from the founders, have a specific goal to Conduct retirement benefits, have their own interests, have a regular organization in the Division of duties and functions between founders, supervisory boards, and managers, and obtain recognition and confirmation from the State authority. While the pension fund as an independent legal entity does not use the form of legal entity such as limited liability company, cooperative, or foundation, because there is a concept in the legal entity that does not conform to the concept of pension funds. Keywords: Legal Subject, Legal Entity, Pension Fund AbstrakUndang-Undang Nomor 11 Tahun 1992 tentang Dana Pensiun menyebutkan bahwa dana pensiun adalah badan hukum yang mengelola dan menjalankan program pensiun yang menjanjikan manfaat pensiun pada saat telah pensiun atau pensiun kepada pesertanya. Sebagai badan hukum, dana pensiun terletak sebagai subjek hukum layaknya manusia, yang memiliki hak dan kewajiban sehingga dapat melakukan perbuatan hukum kepada pihak lain. Dana pensiun berbadan hukum dan dapat melaksanakan kegiatan sejak tanggal persetujuan Otoritas Jasa Keuangan. Dilihat dari teori dan persyaratan badan hukum, badan hukum dana pensiun telah memenuhi persyaratan baik materiil maupun formil dalam pembentukan dana pensiun, seperti memiliki kekayaan yang terpisah dari pendirinya, mempunyai tujuan khusus dalam menyelenggarakan manfaat pensiun, memiliki kepentingan, menyelenggarakan organisasi dalam pembagian tugas dan fungsi antara pendiri, dewan pengawas, dan pengurus, serta memperoleh pengakuan dan pengesahan dari otoritas negara. Dana pensiun sebagai badan hukum mandiri tidak menggunakan badan hukum seperti Perseroan Terbatas, Koperasi, atau Yayasan, karena terdapat konsep dalam badan hukum yang tidak sesuai dengan konsep dana pensiun. Kata Kunci: Subjek Hukum; Badan Hukum; Dana Pensiun